Dìalektna frazemìka âk predmet lìngvokulʹturologčìnogo analìzu - Venžinovič, Natalìâ (Słowiańska frazeologia gwarowa II, 2020)
DIALECT PHRASE STUDIES AS A SUBJECT OF LINGUO CULTUROLOGICAL ANALYSIS The article deals with the overview of the most significant works in dialectal phraseology in which phraseological representation of the language world model in the geographical range is considered as a constituent of a nationwide one. Basing oneself on the views of well-known phrase researchers, the author accentuates the indissoluble link of phrases with the ethnos culture, ascertains the peculiarities of forming the regional world model, clears up the specificity of semantics and structure of the geographical phraseological unit. The acquisitions have been described, in particular of the Transcarpathian phraseologists who traced a line round the peculiarities of motivating dialectal phrases taking into account the spiritual culture of dialect speakers. The link of modern phraseological world model with ancient traditions, rituals of Ukrainians, who populate different regions of Ukraine, has been traced. Following well-known, investigators of phraseology, the author picked out cultural and national connotations of geographical phrases, using contemporary scholarly methods.